Nobody here but me - Viorst, Judith (Farrar Straus Giroux, 2008)
With his mother on the phone, his father checking e-mail, and his sister playing with her friends, a little boy feels as if he is all alone in the house, and no matter how badly he behaves, no one comes to stop him.